beSMART: a software tool to support the selection of decision software - Tereso, Anabela Pereira (2011)
This paper presents a tool which goal is aiding the user to choose the best Decision Support Software between a set of Software residing in a database, according to the features desired, and using multicriteria decision methods. This application was developed using the C# programming language and allows to save in a file all user data, such as the set of Decision Software Tools under consideration and its features to be used afterwards.